Medidas de bioseguridad aplicadas en los trabajadores de los ranarios y peceras del barrio Piuntza Parroquia Guadalupe Cantón Zamora. Año 2015. - Aguilar Lozano, Luz Teresa (2016)
In the work had purpose: To determine the biosecurity measures applied by workers Piuntza frog ponds and tanks at the neighborhood, the sample was 29 workers. The design was cross-sectional, descriptive, prospective field and literature. The technique used was survey and observation instruments questionnaire and direct observation guide. According to the surveys could be identified that within the socio demographic characteristics predominate women 31 to 45 years with 55.17%, marital status married 55.17% of the basic general education 48,28%. Biosecurity measures are: Immunization with 89.66%; guardrails: 86.21% used the caps, the 93.10% wear boots, do not use glasses at 96.55%, the gloves do not apply 86.21% lack 93.10% mask and 96 55% do not use gowns: hygiene: the 89.66% do not wash their hands, 89.66% nails are not cut, the 89.66% do not use antiseptic soap and 65.52% do not have with trash cans; death in post management: the 79.31% do not have this means of disposal. Causes of failure: the 65.52% do not have the necessary material, 44.83% do not use protective clothing. Suffering diseases: mycosis with 37.93% and 17.24% dermatitis, prevention plan in order to raise awareness among workers about the use of protective clothing was raised. It is concluded that most workers do not apply biosecurity measures because they do not have protective clothing where are: Barriers protection, hygiene measures. Keywords: biosecuritymeasures, workers, frogponds, tanks